Restorative Justice di Tingkat Kepolisian atas Tindak Pidana Balapan Liar yang dilakukan oleh Anak: Studi di Wilayah Kepolisian Resor Kota Sampang - Alifia Fitriana Saputra; Yana Indawati (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2024)
This study is designed to understand how the application and implementation of restorative justice serve as a last resort principle for handling cases of illegal street racing committed by minors in the Sampang City Police jurisdiction. The approach used in this study is the empirical juridical method, involving the Conceptual Approach and the Statute Approach. The research questions addressed in this study are: (1) How is restorative justice implemented at the police level for handling cases of illegal street racing committed by minors (a study in the Sampang City Police area)? (2) What are the challenges and efforts in implementing restorative justice at the police level for cases of illegal street racing committed by minors (a study in the Sampang City Police area)? According to the study’s findings, the conclusions are as follows: The first research question explores the implementation and process of restorative justice carried out by the Sampang City Police for cases of illegal street racing by minors. The second research question reveals various obstacles in the implementation of restorative justice at the police level concerning cases of illegal street racing involving minors. Additionally, efforts are being made by the police to prevent illegal street racing committed by minors.